(untitled) (International Journal of Environmental Sciences, 2025)
Introduction: Prehypertension is commonly observed in young adults with anxiety, often leading to increased blood pressure and respiratory rate. Objective: To evaluate the effectiveness of Vajrasana and Padmasana positions combined with diaphragmatic breathing and Jacobson relaxation in young adults with anxiety and prehypertension. Method: Sixty participants were divided into two groups (30 each). Group A practiced Vajrasana, and Group B practiced Padmasana, both with DBE and JRT for 15 minutes, 4 days a week over 8 weeks. BP, RR, and anxiety levels were recorded pre- and post-intervention. Results: Both groups showed significant improvement in RR (p=0.732) and anxiety (p=0.509), but Group A showed greater improvement in systolic (p=0.000) and diastolic BP (p=0.006). Conclusion: While both positions improved RR and anxiety, Vajrasana with DBE and JRT was more effective in reducing blood pressure, showing greater overall benefits.